2020
DOI: 10.1111/jeu.12780
|View full text |Cite
|
Sign up to set email alerts
|

Rosette Colonies of Choanoflagellates (Salpingoeca rosetta) Show Increased Food Vacuole Formation Compared with Single Swimming Cells

Abstract: Choanoflagellates exist as both single‐celled and colonial forms and filter‐feed by generating water currents using a single apical flagellum. Hydrodynamic modeling studies have differed in predictions of whether single cells or colonies produce greater fluid flow to enhance feeding, and a recent study reported no increase in feeding efficiency of stalked colonies of choanoflagellates compared with single cells. We report that rosette colonies of Salpingoeca rosetta demonstrate higher rates of food vacuole for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Several selective factors have been proposed that might have favored the evolution of multicellularity in the ancestors of choanoflagellates and animals (reviewed by Koehl 2020). One suggestion is that multicellularity may have enhanced the rates at which cells in colonies captured bacterial prey (Kirkegaard and Goldstein 2016; L'Etoile and King-Smith 2020;Roper et al 2013;Stanley 1973). It has also been argued that an important selective factor leading to the evolution of multicellularity in the protozoan ancestors of animals was the relative difficulty that protozoan predators may have had in capturing larger multicellular colonies than smaller unicellular prey (Boraas et al 1998;Richter and King 2013;Stanley 1973).…”
mentioning
confidence: 99%
“…Several selective factors have been proposed that might have favored the evolution of multicellularity in the ancestors of choanoflagellates and animals (reviewed by Koehl 2020). One suggestion is that multicellularity may have enhanced the rates at which cells in colonies captured bacterial prey (Kirkegaard and Goldstein 2016; L'Etoile and King-Smith 2020;Roper et al 2013;Stanley 1973). It has also been argued that an important selective factor leading to the evolution of multicellularity in the protozoan ancestors of animals was the relative difficulty that protozoan predators may have had in capturing larger multicellular colonies than smaller unicellular prey (Boraas et al 1998;Richter and King 2013;Stanley 1973).…”
mentioning
confidence: 99%
“…Because unicellular cyst-like cells seemed to have a survival advantage over multicellular flagellates in the hypersaline phase of the evaporation-refilling cycle, we wondered whether multicellularity, by contrast, was advantageous in the other phase of the cycle, marked by low salinity. It has been speculated that multicellularity in choanoflagellates might enhance feeding via cooperative hydrodynamic interactions between flagella, increasing the flux of bacterial prey towards the collar ( 7577 ); however, this concept remains uncertain in the model choanoflagellate Salpingoeca rosetta , with different studies having come to contrasting conclusions ( 75 , 78 , 79 ). To test for a feeding advantage in multicellular sheets of C. flexa , we quantified the capture of fluorescent bacteria in sheets and dissociated single flagellates ( Figure 5B-C ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Kirkegaard and Goldstein (2016) found no enhancement of flux for cells in chains or in rosette colonies (balls of cells with their flagella pointing outward) compared with unicellular choanoflagellates. Experiments showed no effect of multicellularity on feeding rates for choanoflagellates that form hemispherical colonies attached to the substratum by a stalk (Fenchel, 2019), whereas other studies revealed that freely swimming rosette colonies captured more bacteria per cell per time than did unicellular swimmers or unicellular thecate choanoflagellates attached to surfaces (Kreft, 2010; L'Etoile & King‐Smith, 2020). Measurements of choanoflagellate swimming showed that rosette colonies traveled more slowly than did unicellular choanoflagellates (Kirkegaard et al, 2016; Koehl, 2020), but water velocities measured relative to the collars of unicellular swimmers and of cells in rosette colonies showed that some of the cells in colonies encountered much greater water flux than did the single cells (Koehl, 2020).…”
Section: Discussionmentioning
confidence: 98%